Myocarditis in SARS-CoV-2 infection vs. COVID-19 vaccination: A systematic review and meta-analysis - Voleti, Navya; Reddy, Surya Prakash; Ssentongo, Paddy (Frontiers in Cardiovascular Medicine, 2022)
Background: To compare the incidence of myocarditis in COVID-19 vaccines and SARS-CoV-2 infection groups. Methods: Electronic databases (MEDLINE, Scopus, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews and the World Health Organization Global Literature on Coronavirus Disease) and trial registries were searched to April 2022, for randomized controlled trials and observational cohort studies reporting the risk of myocarditis associated with the COVID-19 vaccines and the risk associated with SARS-CoV-2 infection. We estimated the effect of COVID-19 infection and vaccines on rates of myocarditis by random-effects meta-analyses using the generic inverse variance method. Meta-regression analyses were conducted to assess the effect sex and age on the incidence of myocarditis. Results: We identified 22 eligible studies consisting of 55.5 million vaccinated cohort and 2.5 million in the infection cohort. Median age was 49 years (interquartile range (IQR): 38-56), and 49% (IQR: 43% to 52%) were male. Of patients diagnosed with myocarditis, 3.48 (%) were hospitalized and 0.05 (%) died. The relative risk (RR) for myocarditis was 7 times in the infection group than vaccination group (RR: 15 (95% CI: 11.09 - 19.81, infection group) and RR: 2.0 (95% CI: 1.44-2.65, vaccine group). Of patients who developed myocarditis after receiving the vaccine or having the infection, 61 (IQR: 39% -87%) were male. Meta- regression analysis indicated that male sex and young age were associated with myocarditis. A slow decline in the rates of myocarditis was observed as a function of time from vaccination. Risk of bias assessment was moderate. Conclusions: In this systematic review and meta-analysis, we found that the risk of incident myocarditis is about 7 times higher in persons who were infected with SARS-CoV-2 virus than those who received the vaccine. These findings support continued use of mRNA COVID-19 vaccines among all eligible persons aged ≥5 years.